A Fuzzy VIKOR method to analyze the risks in lean manufacturing implementation. (2021) - Bhalaji, R.K.A.; Bathrinath, S.; Saravanasankar, S.
Abstract: Lean manufacturing is a theory, widely identified to gain more profits, reduce waste, and deliver valued products for customers without harming productivity. Albeit, it is a lucrative business trick, but implementation possesses a massive hurdle for success in any organization. Therefore, for the successful implementation of a lean manufacturing system, the factors and the risks involved should be identified and eliminated. This research is a case study of such risks involved in the implementation of Lean Manufacturing system in medical equipment manufacturing firms located in the southern part of India. The identification of risks was made by a literature survey as well as inputs from industry experts and analysis of risk using MCDM methods like Fuzzy Nominal Group Method (NGM) and VIKOR (VIseKriterijumskaOptimizacija I KompromisnoResenje) methods. The outcome of this paper is a selection of the best medical equipment manufacturing firms among a list of firms, based on the implementation of a lean manufacturing system. The proposed outcome of this research work was verified with case companies, existing literature, and consultation with experts. Finally, a sensitivity analysis was used to validate the results from the above methods.